2012
DOI: 10.4103/0019-5545.94641
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of neuropsychiatric illnesses in older age group population: An inpatient study report from Nepal

Abstract: Background:Inpatient institution-based geropsychiatric study reports are rare in the world psychiatric literature.Aims:To study the pattern of neuropsychiatric illnesses seen in older age group population and to study how the advancing age influences the pattern of physical and neuropsychiatric illnesses in these geriatric people.Materials and Methods:This was a retrospective review of the charts of all patients of age 60 years and above, during a specified period of 3.5 years. The present study reports the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…7 Our study is consistent with the finding of another study done by Aich TK et al in which 64.5% were in the age range of 60-69 years, 31.5% of them were in the age range of 70-79 years and the remaining 5.1% patients were aged 80 years or above. 8 In our study, female patients (50.95 %) were slightly more than male patients (49.05 %). This finding is consistent with the study of Pereira YDS et al 5 and also with study by Shakya DR 9 in the same setting in 2009 which showed 54% female patients presenting to psychiatry OPD.…”
Section: Socio-demographic Profile: Age and Sex Distributionmentioning
confidence: 42%
See 1 more Smart Citation
“…7 Our study is consistent with the finding of another study done by Aich TK et al in which 64.5% were in the age range of 60-69 years, 31.5% of them were in the age range of 70-79 years and the remaining 5.1% patients were aged 80 years or above. 8 In our study, female patients (50.95 %) were slightly more than male patients (49.05 %). This finding is consistent with the study of Pereira YDS et al 5 and also with study by Shakya DR 9 in the same setting in 2009 which showed 54% female patients presenting to psychiatry OPD.…”
Section: Socio-demographic Profile: Age and Sex Distributionmentioning
confidence: 42%
“…This data is consistent with the study by Khattri JB et al 11 . Most of the previous studies had shown higher prevalence of psychotic illness like 20.3% in the study by Aich TK et al 8 , 43% in the study by Prasad KMR et al 18 , 43.7% in the study by Bhogale GS et al 19 , 12.2% in the study by Pereira et al 5 , 31% in the study by Gupta S 7 . As in all these studies, the prevalence of psychotic illnesses is much higher than the general community prevalence of about 1%.…”
Section: Psychiatric Morbiditiesmentioning
confidence: 89%
“…Most Indian studies also did not elaborate much on the prevalence of mania in this age group, although one study reported 7.1% mania in their geropsychiatric patient population 19 . Comparatively, an inpatient study from Bhairahawa reported a much higher (15.9%) attendance of mania amongst their geriatric psychiatric patients 11 .…”
Section: Mood Disordermentioning
confidence: 92%
“…INPATIENT DATA COMPARED: 11 . But, current outpatient study revealed Psychosis to be the largest diagnostic group in both male and female geriatric patients, followed by ADS in male and Depression in female patients (Table no 3).…”
Section: Outpatientmentioning
confidence: 99%
See 1 more Smart Citation